Antioxidant and antimicrobial efficacy of giloy (Tinospora cordifolia) stem powder in spent hen meat patties under aerobic packaging at refrigeration temperature (4 ± 1℃). Issue 10 (2nd August 2021) - Kumar, Pavan; Kaur, Simranjeet; Goswami, Mayank; Singh, Sandeep; Sharma, Amit; Mehta, Nitin
Abstract: Spent hen meat patties were prepared by incorporating different levels of giloy stem powder (GSP), namely, Control‐0%, T1%‒2%, T2%‒3%, and T3%‒% and assessed for various quality parameters. The treated patties were recorded with significantly ( p < .05) higher emulsion stability, cooking yield, and height expansion. On sensory analysis, the T2 sample was selected for storage studies along with Control (C) and positive control (PC, 0.02% butylated hydroxytoluene) patties at refrigeration temperature (4 ± 1℃) for 28 days. Throughout the storage period, the lipid oxidation parameters and microbiological parameters were noted significantly ( p < .05) lower for T2 as compared to PC and C samples. The overall acceptability of the T2 sample was noted significantly higher ( p < .05) than PC and C on 21st and 28th days. Thus, GSP incorporation at 3% has the potential to improve the storage stability of meat patties owing to its antioxidant and antimicrobial potency and could be used as a potential alternative to synthetic preservatives in the food system. Novel impact statement: Giloy stem powder (GSP) is a rich source of various bioactive compounds exerting antioxidant and antimicrobial effects. The present study evaluates the antioxidant and antimicrobial potential of GSP in improving oxidative stability of developed spent hen meat patties and explores the possibility of its use as an alternative to synthetic preservatives in food systems.